1999
DOI: 10.1021/je990109q
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Pressures of the Aqueous Desiccants

Abstract: The vapor pressures of the aqueous desiccants lithium chloride, lithium bromide, calcium chloride, ethylene glycol, propylene glycol, and their mixtures were measured at their typical operating concentrations and at temperatures from 298 K to 313 K. The experimental data were fitted to an Antoine type of equation, ln[P(kPa)] ) A -B/[T(K) + C], where A, B, and C are constants and are concentration dependent. Vapor pressure data were further used to predict the effectiveness of dehumidification in liquid desicca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 11 publications
0
51
0
Order By: Relevance
“…The dehumidification effectiveness of the LD was evaluated using an existing model (Equations (10) and (11)) found in the literature [27,28]. The model is an empirical model applicable to an LD unit with a lithium chloride (LiCl) solution.…”
Section: Ld-idecoasmentioning
confidence: 99%
“…The dehumidification effectiveness of the LD was evaluated using an existing model (Equations (10) and (11)) found in the literature [27,28]. The model is an empirical model applicable to an LD unit with a lithium chloride (LiCl) solution.…”
Section: Ld-idecoasmentioning
confidence: 99%
“…The dehumidification effectiveness (ε d ) is simulated by Eq. (6) (Chung and Luo 1999). Equation (6) can be applied with an average error of ±10% (Chung and Luo 1999;Jain and Bansal 2007).…”
Section: Modelling Of the Absorber And Regeneratormentioning
confidence: 99%
“…(6) (Chung and Luo 1999). Equation (6) can be applied with an average error of ±10% (Chung and Luo 1999;Jain and Bansal 2007). Once the dehumidification effectiveness is obtained, the air moisture contents at the outlet of the absorber and regenerator can be calculated by using Eqs.…”
Section: Modelling Of the Absorber And Regeneratormentioning
confidence: 99%
“…For example, Chen et al [15], Patnaik et al [16], McDonald et al [17], Chung et al [18], Potnis and Lenz [19], and Ullah et al [20] carried out experiments on packed bed dehumidifiers, using salt solutions as the desiccants. Chung et al [21], Oberg and Goswami [1], Martin and Goswami [22], Park et al [23], Peng and Howell [24], Chebbah [25], Park et al [26,27], Chung and Luo [28], and Chung and Wu [29] reported some experimental findings using triethylene glycol as the desiccant. Furthermore, Zurigat et al [30] carried out experiments on dehumidifiers with structured packing, using triethylene glycol as the desiccant.…”
Section: Introductionmentioning
confidence: 99%
“…The TEG vapor is thus carried over into the conditioned space and may condense on walls, windows and equipment, forming a viscous film. Furthermore, the viscosities of the glycol are much higher than that of the aqueous salt solutions and the pumping cost is also higher [28]. On the other hand, lithium chloride has good desiccant characteristics and does not vaporize in the air at ambient conditions.…”
Section: Introductionmentioning
confidence: 99%